Time Semantics As an expression in architecture - Khalil ibrahim Ali; Hadeer jassim al-saady (Iraqi Journal of Architecture and Planning, 2009)
The concept of time had stood to confront philosophical studies in severalfields of kaowledge, including archilecture, demanding an understanding of thisphenomenon.Time remained invisible, and only felt by sense, intuition and abstraction;unconnected to architecture as an expression of form.This paper tries to relate time to architecture not as an evolutionary conceptin architectural change but as a factor which evolves with significance in expressiveaspect.It presents findings, which illustrates time as a signifier to architecturalvision and expression.